BIBLIOTECARUL- PROFESIE PE PAGINILE BIBLIOPOLIS-ULUI - COŞERIU, director adjunct, Biblioteca Municipală „B.P. Hasdeu", Tatiana (BIBLIOPOLIS, 2020)
The article is an analyse of the level of presentation on the „BiblioPolis" pages of a librarian profession. The study is made through the contexts: librarian's formation, professional development, profession's researches, librarian activity.